2020
DOI: 10.34256/famr2024
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Tribolium castaneum and quality changes in Oryza sativa by indirect exposure to Non-Thermal Plasma

Abstract: The management of stored product pests is a serious concern as it contributes to postharvest product losses. This study investigated the influence of NTP on the control of Tribolium castaneum adults and the quality of Oryza sativa and compared with phosphine fumigation. The experiments were performed at 100 - 200 V of NTP and 100 - 200 ppm of phosphine for the exposure periods of 8, 16, and 24 h. Mortality of 100 % and 86.67 % was obtained at 24 h of exposure for plasma treatment (200 V) and phosphine (200 ppm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Nevertheless, studies have shown the detrimental effect of gaseous plasma species (excluding the etching effect) on insect mortality. Paul & Mahendran (2020) used indirect (200 V) plasma treatment (gaseous species) for T. castaneum disinfestation and found 100% mortality in adult insects after prolonged exposure of 24 h. Hence, it is possible to achieve mortality in internal feeder pupae but with the increased exposure time as there is no direct etching effect on insects.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, studies have shown the detrimental effect of gaseous plasma species (excluding the etching effect) on insect mortality. Paul & Mahendran (2020) used indirect (200 V) plasma treatment (gaseous species) for T. castaneum disinfestation and found 100% mortality in adult insects after prolonged exposure of 24 h. Hence, it is possible to achieve mortality in internal feeder pupae but with the increased exposure time as there is no direct etching effect on insects.…”
Section: Resultsmentioning
confidence: 99%
“…It states thatcold plasma is efficientagainst microorganisms presentin meat and meat products [7,31,80]. Deactivation of Campylobacter jejuni in chicken ham utilizing the atmospheric-pressure plasma techniqueaccomplishedat radio frequency and using argon gas [46].…”
Section: Meat and Poultry Industrymentioning
confidence: 99%
“…Novel nonthermal approaches like ozonation [9], gamma irradiation [10] and cold plasma are emerging disinfestation techniques. Among which cold plasma is a potential disinfestation method against a wider range of insect species like Myzus persicae [11], Frankliniella occidentalis (Pergande), Frankliniella fusca (Hinds), Aedes albopictus (Skuse), Tetranychus urticae, Blattella germanica (L.) [12], Plodia interpunctella [13] and Tribolium castaneum [14,15]. Plasma composed of free radicals, reactive oxygen and nitrogen species, UV radiation, atoms in their ground, and excited states engenders destructive effects to the insects, thereby resulting in effective insect control.…”
Section: Introductionmentioning
confidence: 99%